TREATMENT RESULTS EVALUATION OF PATIENTS WITH LOWER LIMB ARTERIAL THROMBOSIS AFTER CORONAVIRUS INFECTION - A.A. Irnazarov; U.A. Asrarov; V.R. Khasanov; J.K. Matmuradov (Central Asian Journal of Medicine, 2023)
An analysis of the results of surgical interventions in patients with thrombosis of the arteries of the lower extremities who suffered coronavirus infection was carried out. 42 patients were divided into 2 groups: the primary group, where endovascular thromboaspiration and systemic thrombolysis were performed to, and the control group, thrombectomy was performed to. On patients who undergone thrombectomy, in 2 cases, rethrombosis was detected in the early postoperative period, as well as in 2 cases, there was no regression of ischemia and as a result was performed high amputation. In the primary group, revascularization lead to limited necrotic zone formation in 1 case. Applying of endovascular thrombaspiration and thrombolysis over the thrombectomy significantly reduces the incidence of complications, retrothrombosis and mortality.